(untitled) (Journal of Bangladesh Academy of Sciences, 2024)
The dynamics of laser-induced plasma plumes were investigated using the Doppler effect and the spectroscopic analysis for the first time. Plasma is generated on silver, copper, and gold targets in ambient air at atmospheric pressure and room temperature using laser ablation with a Q-switched Nd: YAG laser. The laser setup included specific parameters: a pulse duration of 8 ns, a repetition rate of 10 Hz, laser pulse energies of 40 mJ, and a grating with 2400 grooves/mm. When the input end of the optical fiber is perpendicular to the sample surface, a Doppler shift in the emitted wavelength occurs. By analyzing this Doppler shift of the emission wavelengths at two distinct source-detector relative positions, we can accurately estimate the velocities of silver, copper, and gold atoms within the laser-induced plasma. J. Bangladesh Acad. Sci. 48(2); 185-191: December 2024